FORMATION OF SYSTEM OF COMPLEX TRAINING EXPERTS IN EDUCATION WITH THE HELP OF INTERACTIVE TECHNOLOGIES - Shchelko, B.O. (Journal of Information Technologies in Education (ITE), 2010)
The article deals with problems of innovation approach to organization of educational process in educational institutions. In the article the questions of usage of interactive technology in learning process are considered.